If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12+y=13
We simplify the equation to the form, which is simple to understand
-12+y=13
We move all terms containing y to the left and all other terms to the right.
+1y=+13+12
We simplify left and right side of the equation.
+1y=+25
We divide both sides of the equation by 1 to get y.
y=25
| 18(t-3)+3t=7(3t+3)-8 | | x+3(x+3)=7(x-3) | | 108s^2-147=0 | | T^2-8t-6t+48= | | 5+x=13 | | 5x=8y+24 | | 12+c-2=21 | | 5x-8y=24 | | x+9=24+3x-x^2 | | 2b-6=m | | 1.8x-4.4-4.8x=-4.0x-5.9 | | 7x-7+5x=-19 | | 16x+4+5x-15= | | 9x^2+9=24+3x-x^2 | | x^2-4y^2-4x=0 | | 4-a=(2a+6)5 | | 3x-(-10)=13 | | x+90=2x | | 15h^2-17hj-4j^2=0 | | 4x^2-11x+3=5x+4 | | -(5y+1)-(-4y-3)=-1 | | (73+75+x)/3=77 | | (73+75+x)/2=77 | | -4x-(-4)=-8 | | 4y+7=5y-3 | | 25a^3+110a^2-75a=0 | | 5x=4y+7 | | 36c^2-12c+1=0 | | 18x^3-12x^2+6x=0 | | x+180=360 | | 12x-2y=59 | | 8x-7y=23 |